Diversity patterns of epiphytic bryophytes across spatial scales: Species‐rich crowns and beta‐diverse trunks. (31st May 2022) - Berdugo, Monica B.; Gradstein, S. Robbert; Guérot, Louise; León‐Yánez, Susana; Bendix, Jörg; Bader, Maaike Y.
Abstract: Tropical forests are highly diverse at many spatial scales. In these forests, small‐sized canopy organisms can form species‐rich communities already within a few cm 2 . Understanding how species numbers increase when expanding the sampling along the tree and the forest is critical for evaluating the processes maintaining biodiversity. We therefore studied epiphytic bryophyte diversity in tree crowns and along trunks across spatial scales in a tropical lowland forest in Amazonian Ecuador, sampling bryophytes in 100‐cm 2 quadrats on 24 trees (15–22 quadrats each) using a spatially hierarchical design, analyzing alpha and beta diversity at different spatial grains and extents. At the smallest grain, tree crowns held more bryophyte species than trunks, but at the largest grain the trunks held most species (93 vs. 77), as beta diversity was higher among trunks than among crowns. However, except for trunks at the largest extent (all 24 trees), the highest beta diversity among quadrats was always found between crowns and trunks. Species turnover strongly dominated beta diversity at all spatial scales. This and the high species richness resulted in highly unpredictable species compositions, especially in trunk communities. These patterns suggest different controls of diversity in crowns than on trunks and an important role for chance processes in shaping these communities. The high beta diversity within trees, in combination with the large effort involved in climbing trees, implies that diversity sampling of small canopy organisms is most efficient using an intensive (many plots on few trees) rather than extensive (many trees across a large area) sampling. Abstract in Spanish is available with online material. Abstract : Forest canopies are highly complex habitats, home to a wide range of organism groups. We observed that spatial scaling of alpha and beta diversity patterns differs between crown and trunk epiphytic bryophyte communities. The evidence we provide contributes to further understanding how processes such as species interactions and environmental filtering determine the diversity patterns. Resumen: Los bosques tropicales son altamente diversos a diferentes escalas espaciales. En estos bosques, pequeños organismos de dosel pueden formar comunidades ricas en especies incluso dentro de unos pocos centímetros cuadrados. Comprender cómo incrementa el número de especies al expandir el muestreo en el árbol y en el bosque es crítico para evaluar los procesos que mantienen la biodiversidad. Por lo tanto, estudiamos la diversidad de briofitos epifitos en las copas y a lo largo de los troncos a través de diferentes escalas espaciales en un bosque tropical de tierras bajas en la amazonia ecuatoriana mediante el muestreo de briofitos con cuadrantes de 100 cm 2 en 24 árboles (con entre 15 y 22 cuadrantes por árbol), implementando un diseño jerárquico en el espacio y analizando la diversidad alfa y beta a diferentes granos y extensiones espaciales. En el grano más fino, las copas albergaron más especies de briofitas que los troncos, pero en el grano más grueso, los troncos albergaron más especies (93 vs. 77) dado que la diversidad beta fue mayor entre troncos que entre copas. Sin embargo, excepto por troncos a la extensión más amplia (los 24 árboles), la diversidad beta fue consistentemente mayor cuando se contrastaron cuadrantes de coronas con cuadrantes de troncos. El recambio de especies dominó la diversidad beta en todas las escalas espaciales. Esto sumado a la alta riqueza de especies resultó en una composición de especies altamente impredecible, especialmente para las comunidades de los troncos. Los patrones observados sugieren que diferentes procesos controlan la diversidad en las coronas y en los troncos y que los procesos aleatorios juegan un papel importante en la conformación de las comunidades estudiadas. La alta diversidad beta entre árboles junto con el esfuerzo asociado a la trepa para acceder al dosel implican que muestrear la diversidad de pequeños organismos de dosel puede ser más eficiente de manera intensiva (con muchos cuadrantes en pocos arboles), más que extensiva (muchos árboles con pocos cuadrantes).